Endobronchial valves for patients with heterogeneous emphysema and without interlobar collateral ventilation: open label treatment following the BeLieVeR-HIFi study. Issue 3 (20th December 2016) - Zoumot, Zaid; Davey, Claire; Jordan, Simon; McNulty, William H; Carr, Denis H; Hind, Matthew D; Polkey, Michael I; Shah, Pallav L; Hopkinson, Nicholas S
Abstract : Outcomes in early trials of bronchoscopic lung volume reduction using endobronchial valves for the treatment of patients with advanced emphysema were inconsistent. However improvements in patient selection with focus on excluding those with interlobar collateral ventilation and homogeneous emphysema resulted in significant benefits in the BeLieVeR-HIFi study compared with sham treated controls. In this manuscript we present data from the control patients in the BeLieVeR-HIFi study who went on to have open label endobronchial valve treatment after completion of the clinical trial (n=12), combined with data from those in the treatment arm who did not have collateral ventilation (n=19). Three months after treatment FEV1 increased by 27.3 (36.4)%, residual volume reduced by 0.49 (0.76) L, the 6 min walk distance increased by 32.6 (68.7) m and the St George Respiratory Questionnaire for COPD score improved by 8.2 (20.2) points. These data extend the evidence for endobronchial valve placement in appropriately selected patients with COPD. Trial registration number: ISRCTN04761234 ; Results.